Prevention of Alzheimer's in Elderly - Marsya, Happy; Ninawati, Ninawati; Kezia, Jenny; Devina Dinata, Yolanda; Juvinto, Juvinto (Devotion : Journal of Research and Community Service, 2025)
The increasing number of elderly individuals across countries has brought about new health challenges, one of which is the rising risk of Alzheimer's disease, characterized by progressive cognitive decline. A major problem identified in this study is the lack of public awareness regarding non-pharmacological preventive measures for Alzheimer’s. The objective of this activity is to educate elderly participants about effective preventive strategies, including physical activity, reminiscence therapy, and proper brain nutrition. The method used was a psychoeducational seminar conducted on May 20, 2025, in Jakarta, with 15 elderly participants. Evaluation was performed using a pre-test and post-test design, analyzed with the Wilcoxon test. Results showed a significant increase in participants' knowledge after the seminar (p = 0.003), with the majority demonstrating improved post-test scores. The findings suggest that community-based health education is highly effective in improving elderly understanding of Alzheimer’s prevention. Collaborative efforts between community organizations and health institutions are needed to expand such outreach. This study also serves as a practical model for community service programs that can be replicated in other demographic contexts to promote brain health literacy and preventive behavior.